Plan de negocio que permita la comercialización de servicios funerarios para animales de compañia en la ciudad de Santiago de Cali. (2022)
The currently business plan has an objective of investigate about the behavior of people who lives in stratum 3, 4, 5 and 6 in the city of Santiago de Cali, the purpose of taking these population is the economic solvency who have between the pet consumers. A descriptive investigation was Carrie out to determine the needs and preferences about the services that they are willing to appeal. To elaborate the business plan, we gather information that was collected from current bibliographical references that were referred to the topic and in general, since the information is limited